Bridging the gap between traditional literature and new digital forms: A practical basis for EFL teachers - Quiroga, Lucía Beatriz (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
The purpose of this work is to present a set of sample activities as a starting point to develop the literary competence through literature and Information and Communications Technologies (ICT) in the English as a Foreign Language (EFL) class. The theoretical framework proposed is a combination of literary and technology-oriented approaches that offer a wide space for transaction, participation and cultural interaction. The practical proposal stems from the author’s teaching experience, and emphasizes the understanding of literary dimensions through personal involvement and the generation of a dynamic space of experimentation. By means of fostering the literary experience in our teaching practices students will be able to form an opinion, judge information, and validate ideas. Literature and ICT constitute an excellent vehicle to achieve that objective.